The Growth of Tiwai (Eleutherine Americana L. Merr.) Under Different Forest Tree Stands in Agroforestry System - Noordiana Herry Purwanti; Taryono Taryono (Agrotechnology Innovation (Agrinova), 2018)
Agroforestry is a method and system of land management involving the simultaneous cultivation of farm crops and trees Land use under forest stands in the community has not been optimal. This research aims to study the growth, yield and qualitatively secondary metabolite content and find the best microclimate based on stand of different forest trees of  Tiwai (Eleutherine americana L. Merr.). The research was carried out at research field of Agrotechnology Innovation Centre at Kalitirto, Berbah, Sleman, Yogyakarta and laboratory of agriculture production, Institute of Agriculture “INTAN” Yogyakarta. Treatments are  combinations of forest tree stand i.e. gaharu, teak, mahogany, and control, and plant spacing factors i.e. 25 x 20 cm and 20 x 20 cm, and arranged in split block design with 3 replications.  Plant height, leaf numbers, bulb weight and productivity were observed and analyzed statistically using analysis of variance approach. The treatment effects are studied by mean comparisons using Duncan Multiple Range Test  with α = 5%. Qualitative data such as flavonoid content were descriptively analyzed. The result showed that there are statistically different growth and yield of Tiwai grown under forest tree stands. Tiwai which was grown under teak and gaharu with density 20 x 20 cm yielded similar productivity with control which is 271 – 331 g/m2 and equal to 578 – 883 kg boulbs/ha. There is different brewed colors from dark red to deep purplish Red. Types of tiwai secondary metabolite were dependent upon tree stands.  At control, and under mahogany and gaharu, more apigenin was observed, whereas  kaempferol and lutenoid were found under teak and gaharu. The tiwai cultivation under tree stands probably provided benefit with the 1.5 B/C ratio in the agroforestry system.